The river of doubt : Theodore Roosevelt's darkest journey - Millard, Candice (Anchor Books, 2005)
The true story of Theodore Roosevelt's harrowing 1914 exploration of one of the most dangerous rivers on earth, a black, uncharted tributary of the Amazon that snakes through one of the most treacherous jungles in the world. Indians armed with poison-tipped arrows haunt its shadows; piranhas glide through its waters; boulder-strewn rapids turn the river into a roiling cauldron. After his humiliating election defeat in 1912, Roosevelt set his sights on the most punishing physical challenge he could find, the first descent of an unmapped tributary of the Amazon. He and his men faced an unbelievable series of hardships, losing their canoes and supplies to punishing whitewater rapids, and enduring starvation, Indian attack, disease, drowning, and a murder within their own ranks. Three men died, and Roosevelt was brought to the brink of suicide. Yet he accomplished a feat so great that many at the time refused to believe it.--From publisher description.